2017
DOI: 10.1038/srep44988
|View full text |Cite
|
Sign up to set email alerts
|

LOXL2 drives epithelial-mesenchymal transition via activation of IRE1-XBP1 signalling pathway

Abstract: Epithelial-to-Mesenchymal Transition (EMT) is a key process contributing to the aggressiveness of cancer cells. EMT is triggered by activation of different transcription factors collectively known as EMT-TFs. Different cellular cues and cell signalling networks activate EMT at transcriptional and posttranscriptional level in different biological and pathological situations. Among them, overexpression of LOXL2 (lysyl oxidase-like 2) induces EMT independent of its catalytic activity. Remarkably, perinuclear/cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 69 publications
3
93
0
3
Order By: Relevance
“…Initial studies suggested that LOXL2 action on tumorigenesis and metastasis could be similar to that of LOX, thus related to its potential ECM crosslinking activity (8, 18, 19). Nevertheless, subsequent studies demonstrated an unconventional action of intracellular LOXL2 in invasion and metastasis (12, 17, 2022), including induction of epithelial to mesenchymal transition (EMT), Snail1 stabilization (a key EMT transcription factor), and activation of the UPR pathway (23, 24). LOXL2/Snail1-mediated repression of E-cadherin and other epithelial genes contributes to the dedifferentiated and metastatic phenotype of squamous cell carcinomas and basal breast carcinoma cells, respectively (12, 20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies suggested that LOXL2 action on tumorigenesis and metastasis could be similar to that of LOX, thus related to its potential ECM crosslinking activity (8, 18, 19). Nevertheless, subsequent studies demonstrated an unconventional action of intracellular LOXL2 in invasion and metastasis (12, 17, 2022), including induction of epithelial to mesenchymal transition (EMT), Snail1 stabilization (a key EMT transcription factor), and activation of the UPR pathway (23, 24). LOXL2/Snail1-mediated repression of E-cadherin and other epithelial genes contributes to the dedifferentiated and metastatic phenotype of squamous cell carcinomas and basal breast carcinoma cells, respectively (12, 20).…”
Section: Introductionmentioning
confidence: 99%
“…LOXL2/Snail1-mediated repression of E-cadherin and other epithelial genes contributes to the dedifferentiated and metastatic phenotype of squamous cell carcinomas and basal breast carcinoma cells, respectively (12, 20). Of note, LOXL2-dependent transcriptional repression and EMT induction in cell culture systems does not require its catalytic activity (12, 17, 24, 25), indicating that, at least, part of LOXL2 unconventional actions in cancer may not depend on ECM remodeling. To date, the implication on LOXL2 in tumorigenesis and metastasis rely on cell model systems with overexpression or knockdown of LOXL2.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of IRE1 was dependent on the sequestering of GRP78 by LOXL2, which resulted in XBP1s‐dependent up‐regulation of Snail1, Snail2, Zeb2 and Tcf3 transcription factors. Inhibition of IRE1 RNase activity, by the small molecule inhibitor 4μ8c, reduced LOXL2‐mediated loss of E‐cadherin and blocked transition to a spindle morphology that is typical of cells post‐EMT [Cuevas et al., ]. These studies indicate that loss of IRE1 signalling should reduce the invasive and migratory capacity of cells by suppressing EMT.…”
Section: The Upr In Tumour Initiation Development and Progressionmentioning
confidence: 99%
“…In a different study of breast cancer, overexpression of lysyl oxidase‐like 2 triggered epithelial‐mesenchymal transition (EMT) in basal‐like breast carcinoma cell lines through the activation of IRE1α and subsequent XBP1 splicing. In these cells, XBP1 was shown to directly induce several EMT‐transcription factors such as SNAI1, ZEB2, and TCF3 . In MM, however, increased levels of the IRE1α‐XBP1 pathway are a survival mechanism that occurs in response to the stress of elevated antibody production and secretion.…”
Section: Ire1α Outputs and Cancer: Xbp1mentioning
confidence: 99%
“…In these cells, XBP1 was shown to directly induce several EMT-transcription factors such as SNAI1, ZEB2, and TCF3. 40 In MM, however, increased levels of the IRE1α-XBP1 pathway are a survival mechanism that occurs in response to the stress of elevated antibody production and secretion. In several studies of MM patients, hyperactivation of IRE1α-XBP1 signaling, or a high ratio spliced to unspliced XBP1 mRNA was again linked to poor prognosis.…”
Section: Ire1α Outputs and Cancer: Xbp1mentioning
confidence: 99%